FUNCTIONAL POLYMER FILM-COATED ELECTRODE AND ELECTROCHEMICALDEVICE USING THE SAME - AHN, SOON-HO; YONG, HYUN-HANG; LEE, SANG-YOUNG; OH, BYUNG-HOON; KIM, SEOK-KOO (2005)
The present invention provides an electrode in which an electrode active material particles as being interconnected are applied on current collector, wherein the interconnected surface of electrode active material particles is coated with a polymer, the polymer being present as an independent phase, while maintaining a pore structure formed among the interconnected electrode active material particles as well as an electrochemical device including the electrode. Also, the present invention provides a method for manufacturing a n electrode coated with a polymer present on an interconnected surface of electrode active material as an independent phase, while maintaining a pore structure formed among the electrode active material particles, which comprises the steps of: (a) coating slurry for an electrode including an electrode active material on a current collector and drying it to form an electrode; and (b) dipping the electrode obtained from a step (a) into a solution containing the polymer dissolved therein and a method for manufacturing an electrochemical device comprising the electrode obtained by the above method. The electrode coated with a polymer as an independent phas e provides an electrochemical device with improved safety and prevents degradation of performance of an electrochemicaldevice.